Relationship between Security and Human Rights in Counter-Terrorism: A Case of Introducing Body Scanners in Civil Aviation - Prezelj, Iztok (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
Changes in security environment after the end of Cold War and 9/11 have strongly affected our security concepts and paradigms. In the field of counter-terrorism, a serious conceptual and practical debate on the relationship between security and human rights and freedoms has begun. The goal of this paper is to reflect on this complex relationship at the conceptual level and introduce the empirical debate on this relationship in the field of civil aviation (case of introducing body scanners). The paper’s results show that the concept of human security usefully integrates the care for human rights and security of individuals. The debate on the potential introduction of body scanners on the European airports was actually a debate on the ways of providing individual human security on the airports with simultaneous concern for other human rights. The output of this debate was a compromise: body scanners can be used at the discretion of individual airports and member states, but are not an obligatory measure on all European airports.